Pemberdayaan Kelompok Wanita Tani dalam Memanfaatkan Pekarangan Rumah Produktif Kelurahan Kamanisan Kecamatan Curug Kota Serang - Agus Sukirno; Nina Fitriyani; Eni Nuraeni; Labib Azka Asysyafiq (Universitas Islam Negeri Siber Syekh Nurjati Cirebon, 2024)
Empowerment is the principle of maximizing the potential of the individual and the environment in order to make more valuable benefits in improving the well-being of the self, the family and the community. Housekeeping becomes profitable when the land is used and managed properly. Market management will be more creative and innovative if training and support are first done. The next step is the Women's Party (KWT) and the people around it can follow up by planting a variety of vegetables and the like in the courtyard of the house. The purpose of the dedication is to open up the insights and knowledge of the peasant women's group in the use of the home market and to foster creativity and innovation in the utilization of the house market to be more productive. The materials needed were vegetable plants, fertilizers, plastic polybags, mulches, nets, water pumps. The methods used are supporting, training, focus group discussion. (FGD). The result of the training activities is the growing awareness of the Women's Group and the community to take advantage of the home market. The participants were equipped with theory and also practiced growing vegetables and methods of maintenance and fertilization. They're quite enthusiastic about the activity. The conclusion is that the Women's Group and the citizens are pleased to be given training and support on the use of the home market. The use of the marketplace in addition to promoting a healthy lifestyle also creates a clean and healthy home market environment.